Cobalt doped JUC-160 derived functional carbon superstructures with synergetic catalyst effect for Li-SeS2 batteries - Jin, Wen-Wu; Li, Hejun; Zou, Jizhao; Zhang, Qi; Inguva, Saikumar; Zeng, Shao-Zhong; Xu, Guozhong; Zeng, Xierong (Elsevier, 2020)
The carbon nanostructures with polar metal/heteroatom co-doping are considered as an effective strategy to improve their electrochemical performances. In this context, the crystal-shape engineering is carried out. Based on a new ‘‘one for six’’ strategy, the JUC-160 having a two-dimensional (2D) zeolitic imidazolate framework is transformed into six different carbon materials. These materials do not need a carbon activation process or template removal process. Instead, after a simple carbonization, a series of metal/heteroatom co-doped carbon materials with novel structures are formed. To be highlighted, this work is the first report of using self-assembled carbon nanostructures/SeS2 composites as cathode materials in the field of Li-SeS2. Moreover, those carbon nanostructures can be effectively tailored by adjusting the method of cobalt doping and the amount of cobalt dopant. Because of the benefits from the novel structures and cobalt/nitrogen co-doping, the dissolution of poly-sulfides/selenides is reduced and a high content of SeS2 (73 wt%) is achieved. The optimized cathode displays an extraordinary cycle performance with a reversible capacity of 820.87 mA h g−1 after 100 cycles, and with reversible charge-discharge efficiency is close to 100%
Keywords: Li-SeS2; Crystal-shape engineering; Self-assembled; ZIF; Cobalt-doped